The Role of History Teachers in the Student Assessment Process Senior High School at SMA Negeri 1 Bolano Lambunu - Moh Fatwa R Andi Taru; Mahfud M Gamar; Haliadi; Minarni Nongtji (Kirana Publisher (KNPub), 2026)
The problems in this paper are (1) What is the educational background of History Teachers at SMA Negeri 1 Bolano Lambunu? (2) How is the Student Assessment Process at SMA Negeri 1 Bolano Lambunu? (3) What is the role of History Teachers' knowledge at SMA Negeri 1 Bolano Lambunu? The objectives of this paper are: (1) To describe the educational background of History Teachers, (2) To describe the student assessment process (3) To explain the role of History Teachers' knowledge on assessment at SMA Negeri 1 Bolano Lambunu. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The research informants were two History Teachers at SMA Negeri 1 Bolano Lambunu and one Student at SMA Negeri 1 Bolano Lambunu. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that: (1) History teachers at SMA Negeri 1 Bolano Lambunu have a Bachelor's degree in History Education that is appropriate to their field of expertise and have participated in various training to improve their competence; (2) The assessment process is carried out comprehensively, covering cognitive, affective, and psychomotor aspects by using a combination of formative and summative assessment methods, as well as various instruments such as written tests, assignments, presentations; (3) History teacher knowledge plays an important role as a foundation in designing valid assessment instruments, providing meaningful feedback, and integrating character education in the assessment process.